Unfolding the Role of BDNF as a Biomarker for Treatment of Depression - Rana, Tarapati; Behl, Tapan; Sehgal, Aayush; Srivastava, Pranay; Bungau, Simona (Journal of molecular neuroscience, 2021)
Depression is a well-known disabling mental illness characterized by sadness, loss of interest in activities, and decreased energy. The symptoms of depression are usually recurrent in vulnerable individuals, and persistence of symptoms significantly impairs individuals’ quality of life. The exact pathophysiology of depression remains ambiguous, though many hypotheses have been proposed. Brain-derived neurotrophic factor (BDNF) has recently been reported to play a vital role in the pathophysiology of depression. BDNF is an important neurotrophic factor found in the human brain and is involved in neuronal growth and proliferation, synaptic neurotransmission, and neuroplasticity. The neurotrophic theory of depression proposes that depression results from reduced BDNF levels in the brain, which can be treated with antidepressants to alleviate depressive behavior and increase BDNF levels. The aim of this review is to provide broad insight into the role of BDNF in the pathogenesis of depression and in antidepressant therapy. The studies mentioned in this review article greatly support the role of BDNF in the pathogenesis of depression and treatment of this disorder with antidepressants. Since abnormalities in BDNF levels lead to the production of diverse insults that amplify the development or progression of depression, it is important to study and explore BDNF impairment in relation to depression, neuroplasticity, and neurogenesis, and increasing BDNF levels through antidepressant therapy, showing positive response in the management of depression.